Large versus Small States in the Eurozone, the Democratic Deficit, and Future Architecture. - Ioannides, Yannis Menelaos. (Tufts University. Tisch Library., 2016)
Slides from a presentation given at the conference "Cyprus: Five Years in the Eurozone," Tassos Papadopoulos Foundation, Nicosia, May 17-18, 2013.